2019
DOI: 10.1142/s0218625x18501676
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON STRUCTURAL, SURFACE MORPHOLOGICAL, OPTICAL, LUMINESCENCE AND UV PHOTODETECTION PROPERTIES OF SOL–GEL Mg-DOPED ZnO THIN FILMS

Abstract: Undoped and magnesium-doped zinc oxide thin films were prepared by the sol–gel method. Results from X-ray diffraction indicated that the films exhibited a hexagonal wurtzite structure and were highly oriented along the [Formula: see text]-axis. The intensity of the (002) diffraction peak increased with increasing the Mg doping concentration. Also, Mg doping inhibited the growth of crystallite size which decreased from 46[Formula: see text]nm to 38[Formula: see text]nm with doping concentration. Morphological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…PL analysis is a valuable tool to get better information regarding impurities, transitions and dopants by studying emission spectra. Quantum size effects affect the physical properties of semiconductor materials at nanoscale, like ZnO changed its optical behavior by increase in quantum confinement observed from PL [ 40 ]. PL spectra of various concentrations of Mg incorporated into ZnO were measured with excitation λ~325 nm at room temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PL analysis is a valuable tool to get better information regarding impurities, transitions and dopants by studying emission spectra. Quantum size effects affect the physical properties of semiconductor materials at nanoscale, like ZnO changed its optical behavior by increase in quantum confinement observed from PL [ 40 ]. PL spectra of various concentrations of Mg incorporated into ZnO were measured with excitation λ~325 nm at room temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PL intensity ratio of UV peak to visible peak is related to the crystal quality of the oxide films. We found that the emission intensity ratio of the Mg 0.1 Zn 0.9 O thin film was higher than that of the pure ZnO thin film, which can be attributed to decrease the defect concentration fraction and improved crystal quality [26].…”
Section: Resultsmentioning
confidence: 83%
“…It is well known that the diffraction peak broadening of polycrystalline metal oxide thin films is associated not only with crystallite size reduction but also lattice strain induced in the thin films [24]. While the ionic radii of the dopant Mg 2+ (0.057 nm) is relatively smaller than that of the host Zn 2+ (0.060 nm), some Zn 2+ ions in the crystal lattice of the host oxide material were easily replaced by Mg 2+ ions (>30 at.%) without changing the crystal structure, proving the possibility of MgZnO solid solution formation [25,26]. The substitution of Mg 2+ ions for Zn 2+ ions slightly distorted the lattice of the ZnO crystal.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[9] Zou et al have also studied and improved the nonlinear optical properties of CoO. [10] For this reason, they have utilized different dopants, such as, Al, [11] Mg, [12] Ga, [13] Co, [14] Fe, [15] and Cu. [13,14] Among all dopants, copper is the most suitable dopant for improving optical properties and it is considered as fast diffusing atoms in the ZnO structure.…”
Section: Introductionmentioning
confidence: 99%